Conflict Transformation in Papua: Challenges and Opportunities for Top-down Special Autonomy Policy - Situmorang, Mangadar (Papua Journal of Diplomacy and International Relations, 2025)
Challenges to bring perpetual peace in Papua remain prevalent. These challenges include overcoming social and economic inequality and incompatibility, reducing the level and intensity of destructive behaviors and actions, and strengthening shared institutions to manage potential and actual violent conflicts. The Special Autonomy Law for Papua in 2001 and 2021 are of great opportunities for having the challenges non-violently managed. These legal instruments are both theoretically and normatively perceived to be effective and fruitful mechanisms in order to transform the conflict and bring peace and development to Papua. With that in mind, the article aims to present the benefits and challenges of special autonomy law implementation in Papua. By mainly relying on secondary data, this research argues that the Special Autonomy Law for Papua and the formation of New Autonomous Regions have positive impacts on social and economic development and offer more opportunities for Papuans to be involved in policy-making processes. However, at the same time, these efforts have produced insignificant results in ending violent conflict in Papua. KEYWORDSConflict Transformation; New Autonomous Regions; Special Autonomy